The Palgrave Handbook of Philosophical Methods
XIII, 698 p.
Keywords: This Handbook contains twenty-six original and substantive papers examining a wide selection of philosophical methods. Drawing upon an international range of leading contributors, it will help shape future debates about how philosophy should be done. The papers will be of particular interest to researchers and high-level undergraduates.